New firm gestation: Conception, birth, and implications for research - Reynolds, Paul; Miller, Brenda (Journal of Business Venturing, 1992)
Efforts to encourage or assist new firms are generally directed toward firms at some stage in the gestation (or incubation) process. Although many new firms come into existence every day, there has been little systematic study of the gestation—conception to birth—process. Alternative conceptions of the gestation process can lead to different procedures for estimating the point at which firms become active participants in the economy. This, in turn, can affect estimates of their contributions and age at “discontinuance.” Analysis of four key events of the gestation process (principal's commitment, initial hiring, initial financing, and initial sales) in more than 3,000 established firms indicates substantial variation in the length and patterns of the gestation process. Not all four events are reported by all active firms (sales is the most prevalent event), and every possible sequence of events is reported. The duration of the gestation period ranges from one month (one-fifth report all events occurring in the same month) to 10 years; 90% report a gestation window of three years or less. Alternative definitions of the birthdate, the date at which the new firm is an active participant in the economy, suggest that any event that involves a transaction or relationship outside the firm (first financing, first hiring, first sales) results in similar survival patterns. Date of first sales appears a suitable indicator of “birth” if only one event is to be used. More complex is identifying the conception of new firms. The most common first event reported is the principal's commitment (or involvement). As this may occur several years before the firm emerges as an economic actor, different research procedures must be used to identify such firms. Representative surveys of adults in the labor force (employed, self-employed, or unemployed) show that one in 30 (3%) appear to be involved in a new firm start-up at any given time. The analysis suggests that the widely varying estimates of new firm survival and contributions may be related, in part, to variation in the criteria used to determine a new firm birth (founding, entrance). The rates of stillborns, discontinuances after conception but during gestation, are not yet clear. Programs, public or private, designed to facilitate new firms should give careful attention to the stage of the gestation process where they plan to make their contribution. Assisting firms at different stages will have different costs; the nature and potential for assistance may vary at different stages of the gestation process.